Evidence Translation in a Youth Mental Health Service: Clinician Perspectives. (19th February 2016) - Bailey, Alan P.; Simmons, Magenta B.; De Silva, Stefanie; Hetrick, Sarah E.; Parker, Alexandra G.
An evidence–practice gap is well established in the mental health field, and knowledge translation is identified as a key strategy to bridge the gap. This study outlines a knowledge translation strategy, which aims to support clinicians in using evidence in their practice within a youth mental health service ( headspace ). We aim to evaluate the strategy by exploring clinicians' experiences and preferences. The translation strategy includes the creation and dissemination of evidence translation resources that summarize the best available evidence and practice guidelines relating to the management of young people with mental disorders. Semi-structured interviews were conducted with 14 youth mental health clinicians covering three topics: experiences with evidence translation resources, preferences for evidence presentation, and suggestions regarding future translation efforts. Interviews were recorded, transcribed verbatim, coded, and analyzed using thematic analysis. Themes were both predetermined by interview topic and identified freely from the data. Clinicians described their experiences with the evidence translation resources as informing decision making, providing a knowledge base, and instilling clinical confidence. Clinicians expressed a preference for brief, plain language summaries and for involvement and consultation during the creation and dissemination of resources. Suggestions to improve the dissemination strategy and the development of new areas for evidence resources were identified. The knowledge translation efforts described support clinicians in the provision of mental health services for young people. The preferences and experiences described have valuable implications for services implementing knowledge translation strategies.